Are industry-funded charities promoting "advocacy-led studies" or "evidence-based science"?: a case study of the International Life Sciences Institute - Sarah Steele; Gary Ruskin; Lejla Sarcevic; Martin McKee; David Stuckler (BMC, 2019)
Abstract Background Industry sponsorship of public health research has received increasing scrutiny, and, as a result, many multinational corporations (MNCs), such as The Coca-Cola Company and Mars Inc., have committed to transparency with regard to what they fund, and the findings of funded research. However, these MNCs often fund charities, both national and international, which then support research and promote industry-favourable policy positions to leaders. We explore whether one industry funded charity, the International Life Sciences Institute ('ILSI'), is the scientifically objective, non-lobby, internationally-credible body that it suggests it is, so as to aid the international health and scientific communities to judge ILSI's outputs. Methods Between June 2015 and February 2018, U.S. Right to Know), a non-profit consumer and public health group, submitted five U.S. state Freedom of Information requests (FOIs) to explore ILSI engagement with industry, policy makers, and/or researchers, which garnered a total of 17,163 pages for analysis. Two researchers explored these documents to assess the activities and conduct of ILSI against its purported objectives. Results Within the received documents we identified instances of ILSI seeking to influence research, conferences, public messages, and policy, including instances of punishments for ILSI bodies failing to promote industry-favourable messaging. We identified ILSI promoting its agenda with national and international bodies to influence policy and law, causing the World Health Organization to withdraw from official relations with what it now considers a private sector entity. Conclusions ILSI seeks to influence individuals, positions, and policy, both nationally and internationally, and its corporate members deploy it as a tool to promote their interests globally. Our analysis of ILSI serves as a caution to those involved in global health governance to be wary of putatively independent research groups, and to practice due diligence before relying upon their funded studies and/or engaging in relationship with such groups.